2019
DOI: 10.7759/cureus.4826
|View full text |Cite
|
Sign up to set email alerts
|

Role of the DECAF Score in Predicting In-hospital Mortality in Acute Exacerbation of Chronic Obstructive Pulmonary Disease

Abstract: Introduction Acute exacerbations of chronic obstructive pulmonary disease (AECOPD) can be fatal. In 2012, a comprehensive score was developed to predict the risk of in-hospital mortality in AECOPD called the dyspnoea, eosinopenia, consolidation, acidemia, and atrial fibrillation (DECAF) score. We conducted this study to assess the value of the DECAF score as a clinical prediction tool that claims to stratify all patients with AECOPD by risk accurately. Methods We conducted a pr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
11
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 11 publications
(11 citation statements)
references
References 13 publications
0
11
0
Order By: Relevance
“… 6 In clinical practice, test with AUC greater than 0.8 is considered to be very reliable. 22 The results showed that the AUC of the DECAF scores was 0.83 for predicting in-hospital mortality and 0.79 for short-term mortality (30 days). This indicates that the DECAF test can be used as a promising prognosis tool with satisfactory SEN and SPE for patients with AECOPD.…”
Section: Discussionmentioning
confidence: 95%
“… 6 In clinical practice, test with AUC greater than 0.8 is considered to be very reliable. 22 The results showed that the AUC of the DECAF scores was 0.83 for predicting in-hospital mortality and 0.79 for short-term mortality (30 days). This indicates that the DECAF test can be used as a promising prognosis tool with satisfactory SEN and SPE for patients with AECOPD.…”
Section: Discussionmentioning
confidence: 95%
“…A recent study found that patients with a DECAF score of four or more are at high risk of mortality. 6 Based on the DECAF score, we ranked participants at four levels: ≤2, 3, 4, and ≥5.…”
Section: Methodsmentioning
confidence: 99%
“…A higher score indicates poorer condition. A recent study reported that patients with a DECAF score of four or higher have a signi cant risk of mortality [6].Based on DECAF score we categorized the participants into four grades:≤2, 3, 4, and ≥5.…”
Section: Decaf Scorementioning
confidence: 99%
“…Assessing in-hospital mortality risk rapidly and accurately by a simple prognostic marker will be helpful in grading nursing care and allocating medical resources. Current prognostic markers about AECOPD include two main categories: in ammation-related makers [2][3][4] and DECAF score [5][6][7]. In ammatory mediators can destroy lung structure and promote neutrophil-related in ammation, which can aggravate the disease and cause death.…”
Section: Introductionmentioning
confidence: 99%